2022
DOI: 10.3389/fpls.2022.945553
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of Purple Leaf Formation in Brassica napus by Integrated Metabolome and Transcriptome Analyses

Abstract: Brassica napus as both oilseed and vegetable, is widely cultivated in China. The purple leaf of B. napus is rich in anthocyanins and can provide valuable nutrients. Although several high-anthocyanin cultivars have been reported, the molecular mechanism underlying anthocyanin biosynthesis in B. napus remains lesser-known. Therefore, in this study, we conducted integrative metabolome and transcriptome analyses in three B. napus cultivars with different leaf colors. Overall, 39 flavonoids were identified (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The role of anthocyanin biosynthesis in the development of purple colouration has been extensively studied in multiple plant species, including tomato (Wang et al 2019), Tetrastigma hemsleyanum (Yan et al 2020a), Brassica (Heng et al 2020, Li et al 2022a, Zhao et al 2022c), tea (Song et al 2022), and wheat (Liu et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The role of anthocyanin biosynthesis in the development of purple colouration has been extensively studied in multiple plant species, including tomato (Wang et al 2019), Tetrastigma hemsleyanum (Yan et al 2020a), Brassica (Heng et al 2020, Li et al 2022a, Zhao et al 2022c), tea (Song et al 2022), and wheat (Liu et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…‘Royalty’ [ 38 ]. Through metabolome analyses, cyanidin was proved to be the main contributor of the purple leaf phenotype in Brassica napus [ 39 ]. In the present study, cyanidin was found to be the major anthocyanin in the leaves of A. commutatum ; however, the composition and proportion of anthocyanin monomers did not significantly affect the leaf color of A. commutatum .…”
Section: Discussionmentioning
confidence: 99%
“…'Royalty' [38]. Through metabolome analyses, cyanidin was proved to be the main contributor of the purple leaf phenotype in Brassica napus [39].…”
Section: Variation In Leaf Anthocyanin and Chlorophyll Contentsmentioning
confidence: 99%
“…Due to the genome complexity compared with Arabidopsis, the regulation mechanism of anthocyanin biosynthesis in B. napus is more complicate and it has not been fully elucidated yet. Although many differentially expressed genes (DEGs) have been reported among rapeseed materials with different seed, leaf, or flower colors [50][51][52]. Hitherto, the functionally reported genes affecting anthocyanin biosynthesis in B. napus are structural genes (e.g., DFR, FLS, and LDOX) [52,53] and transcription regulatory factors (PAP2.A7, BnGL3-1, and WRKY41-1) [54][55][56][57].…”
Section: Biotechnology For Biofuels and Bioproductsmentioning
confidence: 99%